2019
DOI: 10.1111/cmi.13036
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lncRNA‐155 encoded by MIR155HG as a novel regulator of innate immunity against influenza A virus infection

Abstract: Long noncoding RNAs (lncRNAs) are single-stranded RNA molecules longer than 200 nt that regulate many cellular processes. MicroRNA 155 host gene (MIR155HG) encodes the microRNA (miR)-155 that regulates various signalling pathways of innate and adaptive immune responses against viral infections. MIR155HG also encodes a lncRNA that we call lncRNA-155. Here, we observed that expression of lncRNA-155 was markedly upregulated during influenza A virus (IAV) infection both in vitro (several cell lines) and in vivo (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(88 citation statements)
references
References 53 publications
0
82
0
Order By: Relevance
“…responses against viral infections [8]. Additionally, MIR155HG has been revealed to function as an oncogene in the progression of diverse cancers, such as pancreatic cancer, glioblastoma and laryngeal squamous cell carcinoma [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…responses against viral infections [8]. Additionally, MIR155HG has been revealed to function as an oncogene in the progression of diverse cancers, such as pancreatic cancer, glioblastoma and laryngeal squamous cell carcinoma [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…As a general rule, lncRNAs whose expression is altered by the antiviral pathways should show deregulation in response to infection with several other viruses, and/or in response to treatment with IFN and/or different PAMPs. This is the case of lncRNA TSPOAP1-AS1 (TSPOAP1 antisense RNA 1) and MIR155HG (miRNA-155 host gene), upregulated in response to infection with influenza and other viruses and by the dsRNA mimic pI:C (lncRNA TSPOAP1-AS1) [85,86]. Interestingly, lncRNA TSPOAP1-AS1 inhibits IFNβ and ISG transcription, playing a proviral role, whereas MIR155HG functions as an antiviral by inhibiting PTP1B (protein tyrosine phosphatase 1B), resulting in higher production of IFNβ and several ISGs.…”
Section: Lncrnas That Affect the Antiviral Responsementioning
confidence: 99%
“…The potential functions of differentially expressed mRNAs, miRNAs and circRNAs were anlyzed and were closely related to inflammatory response [16]. Recently, increasing studies have indicated that lncRNAs play important roles in inflammatory response [17][18][19][20]. Therefore, we proposed that lncRNAs also might participate in regulating inflammatory response during TGEV infection.…”
Section: Introductionmentioning
confidence: 99%